(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
The objective of this study is to provide informative information to assist practitioners, researchers, and decision-makers in navigating the ever-changing environment of operations management. The constantly shifting terrain of the contemporary corporate world places a premium on strong operations management as an essential component of any organization. It is impossible to satisfy the needs of customers, bring down operating expenses, and achieve operational excellence without first developing a seamless orchestration of resources, processes, and people. Business Intelligence (BI) and Analytics are becoming more important to enterprises as crucial tools for making decisions based on data for them to succeed in the current fast-paced environment.